Birth prevalence of hypospadias and hypospadias risk factors in newborn males in the United States from 1997 to 2012. Issue 5 (October 2018) - Chen, M.J.; Karaviti, L.P.; Roth, D.R.; Schlomer, B.J.
Summary: Background: Hypospadias is a common genitourinary malformation and there are conflicting data on whether its prevalence is increasing. Previous studies have described associations with risk factors including small for gestational age (SGA), multiple gestation birth, environmental influences, and maternal factors. Objective: The objective of this study was to examine birth prevalence of hypospadias and hypospadias risk factors in a large national dataset and to evaluate for changes from 1997 to 2012. We hypothesized that any increase in the birth prevalence of hypospadias would be associated with an increase in risk factors such as SGA, prematurity, or multiple gestation birth. Study design: The Kids' Inpatient Database was used to generate national estimates for prevalence of males born with hypospadias, SGA, prematurity, or to a multiple gestation and then prevalences were evaluated for association with time . Multivariable logistic regression was used to evaluate whether birth prevalence of hypospadias was associated with increasing year, SGA, prematurity, and multiple gestation birth. Results: The estimated birth prevalence of hypospadias increased from 6.1 per 1000 births (95% confidence interval [CI] 5.9 to 6.3) to 6.8 per 1000 births (95% CI 6.7 to 7.0), an 11.5% increase from 1997–2012 ( P = 0.014). Among male births, the prevalence of SGA increased 74%, multiple gestation increased 25%, and prematurity increased 20% ( P < 0.001 for all) (Summary Figure). A risk factor was seen in around 20% of males born with hypospadias. Hypospadias birth prevalence also increased in males without risk factors but was not statistically significant (9.1% increase, P = 0.5). On multivariable logistic regression, being born SGA (odds ratio [OR] = 3.3), to a multiple gestation (OR = 1.1), or premature (OR 1.9) were associated with increased odds of hypospadias ( P < 0.01 for all), whereas increasing year was not ( P = 0.3). Conclusions: The estimated birth prevalence of hypospadias in the United States increased from 6.1 to 6.8 per 1000 births from 1997 to 2012. Known hypospadias risk factors of SGA birth, multiple gestation birth, and premature birth also increased over this time to a higher degree. About 20% of males born with hypospadias had one of these risk factors. The birth prevalence of hypospadias in males without any studied risk factors also increased, but this was not statistically significant. More studies are needed to evaluate whether this increase in hypospadias prevalence is due to increases in known hypospadias risk factors, new environmental exposures, improved diagnosis at birth, some combination, or unrelated causes. Summary Figure Birth prevalence of hypospadias, SGA births, multiple gestation births, and premature births from 1997 to 2012. Prevalence is shown in number per 1000 male births. SGA = small for gestational age.